Comparison of anterior, posterior, and anterior combined with posterior surgical treatment of thoracic and lumbar spinal tuberculosis: a systematic review - Bian, Zhouliang (J Int Med Res, 2019)
BACKGROUND: This study was performed to compare different surgical approaches in the treatment of spinal tuberculosis. METHODS: We conducted a literature search to identify and analyze papers published from January 1966 to April 2018 relevant to comparison of the anterior, posterior, and anterior combined with posterior approaches in the treatment of spinal tuberculosis of the thoracic and lumbar regions. RESULTS: Twenty-five studies involving 2295 patients were identified in this systematic review. The operative time was significantly longer in the anterior combined with posterior approach than in the other two approaches. Blood loss was significantly greater in the anterior combined with posterior approach (1125.0 ± 275.5 mL) than in the posterior approach (710.4 ± 192.4 mL). The difference in correction of the kyphosis angle among the three procedures was not significant. The overall surgical and transthoracic complications were significantly lower in the posterior approach. The clinical outcome of all patients improved, but there was no significant difference among the three procedures. CONCLUSIONS: Blood loss, overall surgical and transthoracic complications, and the operative time are different among the three approaches. Therefore, different factors must be carefully assessed in deciding among the three procedures.